2018
DOI: 10.1186/s40644-018-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Cement pulmonary embolism as a complication of percutaneous vertebroplasty in cancer patients

Abstract: BackgroundVertebroplasty is a minimally invasive procedure commonly performed for vertebral compression fractures secondary to osteoporosis or malignancy. Leakage of bone cement into the paravertebral venous system and cement pulmonary embolism (cPE) are well described, mostly in patients with osteoporosis. Little is known about the clinical sequelae and outcomes in cancer patients. In this study, we report our experience with cPE following vertebroplasty performed in cancer patients.MethodsRecords of all cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…On the contrary, Blinc et al (16) performed an in vitro study and demonstrated that the surface of fresh or old cement does not accelerate platelet aggregation or plasma coagulation. In addition, patients with PCE received no anticoagulation therapy and remained asymptomatic during long-term follow-up (17,18), indicating that asymptomatic PCEs may be effectively managed with careful observation. Our results also demonstrated that patients with asymptomatic peripheral or central embolisms could be safely managed with careful observation and clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Blinc et al (16) performed an in vitro study and demonstrated that the surface of fresh or old cement does not accelerate platelet aggregation or plasma coagulation. In addition, patients with PCE received no anticoagulation therapy and remained asymptomatic during long-term follow-up (17,18), indicating that asymptomatic PCEs may be effectively managed with careful observation. Our results also demonstrated that patients with asymptomatic peripheral or central embolisms could be safely managed with careful observation and clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Mansour et al (2) recently published a paper regarding 102 cancer patients with vertebral fractures who underwent vertebroplasty with PMMA injection. Cement PCE was detected in 12.7% of patients; of these, 76.9% had malignant fractures, and the remaining 23.1%, a number of which had active cancer, had osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon kyphoplasty is a minimally invasive surgical procedure that allows the stabilization of compressive vertebral fractures (1). Patients with cancer represent a high-risk group for these fractures, considering not only the underlying disease, but also the prevalence of risk factors for osteoporosis in this population, including advanced age and corticosteroid therapy (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, this minimally invasive treatment had been promoted as a stable treatment for osteoporotic vertebral compression fractures that can not be relieved by conservative treatment. As a routine method for the treatment of osteoporotic vertebral compression fractures, pvp can stabilize the spine and effectively relieve short-term pain [7][8][9]. However, its disadvantages as a common surgical method are still obvious: systemic complications of vertebroplasty are rare; fat embolism or arterial embolism may occur,;and epidural bleeding can also take place, but it is extremely infrequent [10,11].…”
Section: Introductionmentioning
confidence: 99%